Computer methods in biomechanics and biomedical engineering : proceedings of the 14th International Symposium CMBBE, Tel Aviv, Israel, 2016 /: proceedings of the 14th International Symposium CMBBE, Tel Aviv, Israel, 2016. ([2018]) - Unknown
No abstract available